Políticas e práticas de gestão de pessoas em prol da inovação no setor público - Saldanha, Cristina Camila Teles (2019)
This dissertation aims to understand how are perceived the policies and practices of People Management that can encourage innovation in the public sector. Through the relationship of people management and innovation, having the public administration reform as background, an analysis scheme was elaborated in which the professionalization of the public service is a bridge between these three axes. The policies and practices of people management have been systematized in analytical dimensions and represent aspects underlying innovation, such as: Work Organization, Development Policies, Compensation Policies, Traditional / Human Resources Functional Policies, Integration of Functions / Actions of Human Resources and Leadership. Through a study of a qualitative and descriptive nature, the variables present in the analysis dimensions (Autonomy, Flexibility, Rotativity of tasks, Organizational mobility, Work teams, Networks, Delegation of responsibility or decision, Training and education programs, Training and training programs, Incentive systems, Compensation or payment by performance variable, Recruitment and selection) were evaluated through documentary analysis and the perceptions of 15 interviewees of federal and state public organizations and by representatives of the Third Sector . These perceptions about the variables were punctuated by the interviewees on a continuous subjective scale present in the script of semi-structured interviews. The findings of the research demonstrate that respondents' perceptions that variables such as ‘teamwork’, ‘networks’ and ‘leadership’ contribute to innovation in the Brazilian public sector while ‘performance variable pay’ and ‘recruitment and selection’ do not results. Some variables were perceived relatively, such as ‘education and schooling’, ‘professional qualification and training programs’ and ‘incentive system’, since each interviewee interpreted them according to their experience and their values. Moreover, the complementarity of HR functions and practices and the adoption of these practices in a compiled way were not detected. Therefore, can be conclude from the research that there is a lack of an integrated and systemic model of people management in Public Administration from the public consulted, as a result of the budget constraint scenario and the change of government management in the dynamics of innovation in the public sector, as well as the absence of organizational support for the innovation strategy.